Relative Cleanability and Sanitization of Blueberry Mechanical Harvester Surfaces - Renee M. Holland; Laurel L. Dunn; Jinru Chen; Himabindu Gazula; Jonathan E. Oliver; Harald Scherm (Horticulturae, 2022)
Berry crops are increasingly being harvested mechanically to reduce labor costs, but there is a lack of research on best practices for cleaning and sanitizing of mechanical harvesters to maintain proper food hygiene. Laboratory experiments were conducted with surface coupons cut from materials commonly used on blueberry harvesters, including polyethylene, high-density polyethylene, aluminum, extruded polycarbonate, acetal plastic, and stainless steel. Surfaces differed in their hydrophobicity and surface roughness, ranging from 0.04 µm for polycarbonate to 1.57 µm for acetal plastic. The relative cleanability of the surface coupons was assessed by determining the removal of an applied mock soil (dried blueberry puree) in a rinsing-shaking assay with distilled water at room temperature. Results showed that the amount of soil removed increased over time according to a negative exponential function, from 29.6% at 30 s to 40.3% at 240 s rinse time. Compared with the time effect, the differences in soil removal among surfaces were relatively small. The addition of cleaning agents and detergents did not improve soil removal, and the only treatment that removed significantly more soil than the water control was heated (50 °C) distilled water. In sanitization assays, three representative microorganisms were allowed to attach to surface coupons, then exposed to three different sanitizers (0.25% bleach with 200 ppm free-chlorine sodium hypochlorite, 0.30% SaniDate 5.0, or 1.0% No-Rinse Food Contact Cleaner Sanitizer). There was no significant surface effect on microbial reductions following sanitizer treatment. For Bacillus amyloliquefaciens, none of the sanitizers significantly reduced population densities below the water control. In contrast, surface populations of Rhodoturula mucilaginosa and Epicoccum nigrum were reduced significantly by all three sanitizers, with SaniDate (23.0% hydrogen peroxide + 5.3% peroxyacetic acid) resulting in the greatest reduction.